Design of Fuzzy Logic-Based ARDS Berlin Definition for Ventilator Adjustments to Ensure Lung Protection - Wanzala, Jimmy Nabende; Atim, Michael Robson; Obungoloch, Johnes (International Journal of Fuzzy Systems, 2023)
The studies done on lung protective strategies in medical ventilators have shown that tidal volume of 6-ml/ kg predicted body weight protects the lungs of a patient during the invasive ventilation for acute respiratory distress syndrome (ARDS) patients in intensive care unit. Corona virus disease 2019 has increased the need for mechanical ventilation, which are operated manually, in changing the settings on the mechanical ventilators. In this study, fuzzy logic method is used to develop a computer-aided decision making to improve on the accuracy of the reasoning done during the ventilator setting adjustment, by adding the fuzzy reasoning concept into the ARDS Berlin definition. The ARDS positive end-expiratory pressure (PEEP) values were used in building the fuzzy rules of the fuzzy algorithm. From the experimental results, the algorithm mimics the recommended ARDS PEEP values with respect to the values of fraction of inspired oxygen (FiO2); the algorithm as well increases the respiratory rate and tidal volume for potential of Hydrogen (pH) less than 7.2; maintains the respiratory rate and tidal volume for pH between 7.2 and 7.4; decreases the respiratory rate; and maintains the tidal volume for pH greater than 7.4. The developed fuzzy system can therefore be applied as a physician–ventilator interface to guide the clinician/physician during the ventilation, so as, to reduce the human errors and ensure lung protection.
Keywords: Medical ventilation; Fuzzy logic; COVID-19 ARDS; ARDS; ARDS Berlin definition; ARDS Kigali definition